Implementation Patterns of AquaSim for Simulation of Underwater Acoustic Wireless Sensor Networks - Hashim Kraidi Al-Saedi, Karim (Wasit Journal of Computer and Mathematics Science, 2021)
Now days, a number of corporate as well as social applications are connected with wireless technologies which are covered under the domain of Internet of Things (IoT) and Cloud of Things (CoT). To work with the development and implementation of these scenarios, there is need of high performance costly gadgets which are difficult for the self finance researchers and small organizations. To cope up with the financial aspects of developing and getting the results from advanced wireless environment, the use of simulators and software libraries is done. In wireless environment, the segment of Underwater Wireless Sensor (UWSN) or Underwater Acoustic Network (UAN) is quite prominent which are used for the underwater applications including Military, Naval and Underwater Surveillance. Underwater sensor networks are famous for researchers and engineers in wireless technology. This field offers a lot of academic work in different disciplines. The main challenge of this UWSN is the energy saving for sensor nodes. For this cause, the location of sensor nodes shifts about regularly. There are several algorithms for energy production and collection, but this area is still in need of study due to political and national security concerns.
Keywords: Wireless Sensor Networks; Wireless Acoustic Networks; Underwater Sensor Networks